Mutations in glucocerebrosidase are a major genetic risk factor for Parkinson's disease and increase susceptibility to dementia in a Flanders-Belgian cohort. (26th August 2016) - Crosiers, David; Verstraeten, Aline; Wauters, Eline; Engelborghs, Sebastiaan; Peeters, Karin; Mattheijssens, Maria; De Deyn, Peter P.; Theuns, Jessie; Van Broeckhoven, Christine; Cras, Patrick
Highlights: GBA mutations are a strong genetic risk factor for Parkinson disease (PD). A heterozygous GBA mutation was identified in 4.5% of PD patients. More severe PD motor symptoms are observed in GBA mutation carriers. GBA mutation status is an independent predictor for dementia in PD patients. Abstract: Objective: To investigate the frequency of glucocerebrosidase ( GBA ) mutations in a Flanders-Belgian Parkinson's disease (PD) patient cohort and to assess genotype-phenotype correlations. Methods: We performed an in-depth sequencing of all coding exons of GBA in 266 clinically well-characterized PD patients and 536 healthy control individuals. Results: We identified rare, heterozygous GBA mutations in 12 PD patients (4.5%) and in 2 healthy control individuals (0.37%), confirming the genetic association of GBA mutations with PD in the Flanders-Belgian population (p < 0.001). The patient carriers had a more severe Unified Parkinson's Disease Rating Scale (UPDRS) motor score than non-carriers. Also, GBA mutation status was a significant, independent predictor for the presence of dementia (OR = 12.43, 95% CI: 2.27–68.14. p = 0.004). Genetic association of PD with the common p.E326K and p.T369M variants in GBA was absent. Conclusion: In our Flanders-Belgian cohort, carrier status of a heterozygous GBA mutation was a strong genetic risk factor for PD. The GBA mutation frequency of 4.5% is comparable to previously reported data in other European PD patient cohorts. Furthermore, our clinical data suggest a more severe motor phenotype and a strong predisposition to dementia in GBA mutation carriers.